A CORRELATIONAL STUDY BETWEEN WRITING HABIT AND WRITING SKILL OF SIXTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA IN THE ACADEMIC YEAR 2006/2007 - TISNA W , PURWATI (2007)
This research paper is aimed at knowing whether or not there is correlation between writing habit and writing skill of sixth semester student of English department of Muhammadiyah University of Surakarta. There are some factors in writing habit such as the people's desire, motivation, interest, and attitude. The subject of this research is the sixth semester students of English department of Muhammadiyah University of Surakarta. There are 300 students from six classes in this university. The writer uses cluster random sampling in taking sample, and she get 50 students from class C. In collecting the data, the writer gives questionnaire and writing test. The construct validity is used to know the validity of items by using correlation product moment, then to know the reliability the writer uses Alpha Cronbach. The correlation product moment is used to analyze the data. Based on the data calculation, it shows that the obtained rxy is 0.423 when rtable is 0.279 at level of significance 0.05. If the obtained r xy is higher than r table, the obtained rxy 0.423 is positive. So there is positive correlation between writing habit and writing skill. The contribution of writing habit in increasing writing skill is 1,79%. It means that writing habit has role in increasing writing skill, although in contributes small percentage. Finally, the writer finds out that there is positive correlation between writing habit and writing skill of the sixth semester students of English department of Muhammadiyah University of Surakarta.